Effect of Using Effective Microorganisms EM-1 on the Performance of Extended Aeration Activated Sludge in Treating Domestic Wastewater - Waleed M. Sheet (Tikrit Journal of Engineering Sciences, 2009)
This research concerning with the effect of using the effective microorganisms on the efficiency of extended Aeration Activated Sludge Units which consist from many strain of Bacteria, Fungi and Actinomycetes in addition to board spectrum of nutrient and elements which important to growth, The use of this product is practically applied by using two bench scale laboratory units where they are operated to treat the wastewater after completing and preparing the activated sludge units to work under the same conditions of temperature and detention time (DT).